2016
DOI: 10.1002/jca.21504
|View full text |Cite
|
Sign up to set email alerts
|

QTc prolongation during peripheral stem cell apheresis in healthy volunteers

Abstract: QTc prolongation may develop during leukopheresis, particularly if the procedure takes more than 2 h. Thus, to enhance donor safety, QTc measurement should be standard for all donors. In addition, any family history of sudden death should be noted, to prevent the development of possible fatal arrhythmia in susceptible donors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Interestingly, Korur et al 35 showed that QTc prolongation and related complications can develop during leukapheresis, particularly if the procedure takes more than 2 h. One of our patients experienced idiopathic dyspnea, which may be related to the extended apheresis time. Problems with unknown causes during apheresis electrocardiogram records should be checked carefully.…”
Section: Discussionmentioning
confidence: 73%
“…Interestingly, Korur et al 35 showed that QTc prolongation and related complications can develop during leukapheresis, particularly if the procedure takes more than 2 h. One of our patients experienced idiopathic dyspnea, which may be related to the extended apheresis time. Problems with unknown causes during apheresis electrocardiogram records should be checked carefully.…”
Section: Discussionmentioning
confidence: 73%
“…Various cardiac complications developed easily in cases with QTD prolongation after chemotherapy, in particular, in the hematopoietic cell transplant region [12,22,24,38]. Although studies showing the association between blood collecting flow during leukocyte apheresis and QTD prolongation are limited, hypocalcemia due to citrate has been reported to cause QTc prolongation [10,31,[39][40][41]. Prolongation of QTc is also recognized as a marker of sub-physiological plasma-ionized calcium values and a sensitive marker of citrate toxicity at the myocardial tissue level [31].…”
Section: Discussionmentioning
confidence: 99%
“…The most common complications are related to venous access, vasovagal reactions, hypocalcemia symptoms from the citrate anticoagulant, and allergic reactions in response to replacement fluids [5]. Prophylactic calcium supplementation (to avoid citrate toxicity) and prophylactic antihistamine and/or hydrocortisone are administered as safety procedures [5,10]. However, similar to the demands of blood donation, the patients or donors must be healthy for successful leukocyte apheresis [11].…”
Section: Introductionmentioning
confidence: 99%